Detecting plant spatial pattern change after disperser loss: A simulation and a case study. Issue 3 (12th June 2019) - Nield, Andrew P.; Enright, Neal J.; Ladd, Philip G.; Perry, George L. W.
Abstract: Disruption of seed dispersal processes may affect plant population spatial structure. We used a spatial simulation model and an empirical case study to assess the conditions under which the loss of seed dispersers has a detectable effect on a species' spatial pattern. Our simulation experiments suggested that detecting spatial change following disperser loss will be difficult, except when rates of fruit removal are initially high and then completely disappear. To contextualize the simulation modeling, we used spatial point pattern analyses to characterize the spatial pattern of two large‐seeded species ( Leucopogon nutans, a fire‐killed seeder shrub and Macrozamia riedlei, a long‐lived, resprouting cycad) in the jarrah ( Eucalyptus marginata ) forests of southwestern Australia. The plant species' primary disperser, the emu ( Dromaius novaehollandiae ), was absent from one of the sites we considered, but present at the other two. There was no detectable difference for either plant species in the strength of aggregation between sites with and without emu. However, even if disperser loss may not greatly affect local spatial structure for most plant species, it is likely to be important for long distance dispersal and genetic structuring of populations, so accurate characterization of the dispersal kernel is critical, especially in terms of plant emigration. Abstract : There is considerable concern about the implications of the loss of animal dispersers for plant populations. Here, we use a spatial simulation model and field‐based studies to show the difficulties in detecting the loss of dispersers from snapshot spatial patterns describing plant populations. The Emu silhouette in this image is from Phylopic (Darren Naish and T. Michael Keesey).